Evaluación de la percepción y adaptabilidad climática en fincas cacaoteras de la parroquia Ricaurte, bajo un enfoque de adaptación basada en ecosistemas - Sabando Vera, Emely Noemí (2025)
The research aimed to evaluate the perception and adaptability to climate change on cocoa farms in the Ricaurte parish, Chone canton, to identify ecosystem-based adaptation (EbA) strategies. Twenty-four farms belonging to the COOPROACAFRUCHO cooperative were involved, applying structured surveys, direct observation, and quantitative and qualitative methods to understand the socioeconomic, environmental, and productive context of the sector. In the first phase, information was gathered on climate perception, production status, and post-harvest waste generation. In the second phase, the farms' adaptability, vulnerability, resilience, and climate risk level were assessed using methodologies such as the Adaptation Equivalence Index (AEI) and traffic light systems to interpret physical, social, and biophysical indicators. The EbA practices implemented were also identified. Finally, a guide to sustainable strategies was developed based on the findings. 91.67% of producers perceive impacts of climate change, particularly rising temperatures and altered rainfall. Sixty-six percent of farms showed medium adaptability, and 96% showed medium resilience. The most common EbA practices were water conservation, reforestation, and mulching. It is concluded that strengthening these actions improves the cocoa system's response to climate change.